Empowering migrant groups to improve competitiveness of featured products in Kendalrejo Village, Banyuwangi Regency - Nuraini Lusi; Asmaul Khusna; Adetiya Prananda Putra; Wartini Wartini (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Pelangi Migrant is a community consisting of former female workers who work abroad, and it is established at the end of 2018. This group has superior products, namely woven bags made from plastic and various processed foods based on home industries. The average production created in 2019 was around 1500 bags per month, and during this Covid-19 Pandemic, the Pelangi Migrant group could only produce about 500 per month. The production of processed dragon fruit lunkhead is also affected by the Covid-19 pandemic, which originally made 70 Kg/month. During this pandemic, it was only able to produce 25 Kg/month. The main objective of this activity is not only to focus on increasing income but for the village, a village identity or village characteristic will also be formed, which will become a branding in the formation of superior village products focused on the center of woven bag crafts. The activities carried out were training on woven bags made from jali, business management training, branding, digital marketing, and appropriate technology in the production process of processed Dodol. This activity results in increased creativity and productivity of the community, and income also increases.